THE TEACHING PACKAGED DEVELOPMENT ON COEXISTENCE IN SOCIETY ACCORDING TO THE FOUR BRAHMAVIHĀRA DHAMMAS BY USING THE CREATIVE CAI MODEL FOR THE SECOND YEAR LOWER SECONDARY SCHOOL STUDENTS IN YANG TALAT WITTAYAKARN SCHOOL, KALASIN PROVINCE - Yondan, Rungnapha; Saengsai, Paryoon (Journal of Buddhist Education and Research (JBER), 2022)
The objectives of this research were: 1) to study the teaching packaged development; 2) to compare the learning achievement of before and after using the teaching packaged on coexistence in society according to the Four Brahmavihāra Dhammas by using the creative CAI model of the second year lower secondary school students in Yang Talat Wittayakarn School, Kalasin province. 3) to assess satisfaction of the second year lower secondary school students in Yang Talat Wittayakarn school Kalasin Province. It is R&D research The samples of this study included 36 second-year lower secondary school students in Yang Talat Wittayakarn School. The tools used in this research were a teaching packaged, a learning achievement test, and a behavioral assessment form. The statistics used in data analysis were: Frequency, Percentage, Mean, Standard Deviation, and t-test. The research results were as follows: 1) The teaching packaged development on coexistence in society according to the Four Brahmavihāra Dhammas using the creative CAI model for second-year lower secondary school students in Yang Talat Wittayakarn School, Kalasin Province was rated at a moderate level. Based on the testing after the course, students could answer the Dhamma test well. 2) Based on comparing students’ learning achievement before and after using the teaching packaged on coexistence in society according to the Four Brahmavihāra Dhammas by using the creative CAI model, the post-test score of the students was higher than the pre-test score with the statistical significance level of 0.05. 3) The satisfaction of second year lower secondary school students towards the teaching package that the overall, It was at a good level, when considering each aspect, it was found that The mean was at a good level. The aspect with the form/topics of the activities were appropriate and the aspect with the lowest average was the aspect of organizing public relations activities.